The Relationship between Argumentation Skills and Cognitive Flexibility of Pre-Service Science Teachers - Cankaya, Ozlem; Aydogan, Nilay (Asian Journal of Education and Training, 2022)
The present study aims to investigate the relationship between pre-service science teachers’ argumentation skills and cognitive flexibility levels. Within the scope of the study, an argumentation-based science laboratory application was applied to first year science teaching students for 4 weeks. The arguments were assessed by eight faculty members and doctoral students. The Argumentation Assessment Rubric (Choi, 2008) was used to assess the quality of the written arguments. The quality of the arguments and descriptions used by the students in the reports were evaluated as total writing scores. The “Cognitive Flexibility Inventory” developed by Dennis and Vander Wal (2010) was employed to assess the cognitive flexibility levels of pre-service teachers. Simple Correlation analysis and Simple Linear Regression analysis methods were used to determine the relationship between the sub-dimensions of cognitive flexibility inventory and argumentation skills of pre-service science teachers and the effect of cognitive flexibility levels on argumentation skills. The results showed that there was a significant relationship between pre-service teachers’ cognitive flexibility levels and argumentation skills.